2011
DOI: 10.1371/journal.pone.0023137
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hospital-Acquired Infections by Scoring System with Simple Parameters

Abstract: BackgroundHospital-acquired infections (HAI) are associated with increased attributable morbidity, mortality, prolonged hospitalization, and economic costs. A simple, reliable prediction model for HAI has great clinical relevance. The objective of this study is to develop a scoring system to predict HAI that was derived from Logistic Regression (LR) and validated by Artificial Neural Networks (ANN) simultaneously.Methodology/Principal FindingsA total of 476 patients from all the 806 HAI inpatients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 39 publications
(52 reference statements)
4
36
0
Order By: Relevance
“…However, adverse drug reactions (ADRs) occur in 30% to 87% of the patients treated with BZN (19-21), and 12% to 29% of patients fail to complete their full course of treatment (19-21). Therefore, the development of tools to identify patients with high probabilities of developing ADRs to BZN is highly desirable, as this strategy would improve compliance to BZN treatment and minimize complications (21,22).Logistic regression (LR) is a method often used to predict outcomes in health studies (23,24), and it can be used to identify which variables are associated with the occurrence of ADRs to BZN. Therefore, the present study aimed to identify predictive factors for ADRs and ADRs that caused BZN treatment to be discontinued among patients with chronic Chagas disease treated with BZN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, adverse drug reactions (ADRs) occur in 30% to 87% of the patients treated with BZN (19-21), and 12% to 29% of patients fail to complete their full course of treatment (19-21). Therefore, the development of tools to identify patients with high probabilities of developing ADRs to BZN is highly desirable, as this strategy would improve compliance to BZN treatment and minimize complications (21,22).Logistic regression (LR) is a method often used to predict outcomes in health studies (23,24), and it can be used to identify which variables are associated with the occurrence of ADRs to BZN. Therefore, the present study aimed to identify predictive factors for ADRs and ADRs that caused BZN treatment to be discontinued among patients with chronic Chagas disease treated with BZN.…”
mentioning
confidence: 99%
“…Logistic regression (LR) is a method often used to predict outcomes in health studies (23,24), and it can be used to identify which variables are associated with the occurrence of ADRs to BZN. Therefore, the present study aimed to identify predictive factors for ADRs and ADRs that caused BZN treatment to be discontinued among patients with chronic Chagas disease treated with BZN.…”
mentioning
confidence: 99%
“…Torii et al (2003) emphasized that even low concentrations (10 times lower than safety level) of Ligionella pneumophila found in the water used for washing is pathogenic and can cause serious infections in immunocompromised patients (Torii et al, 2003). Furthermore, Legionnaires' disease is estimated to be present in 3 to 15% of community acquired pneumonia and 10 to 50% of nosocomial infections in European countries and the United States (Chang et al, 2011). It has been reported that about 36% of the water samples are contaminated with L. pneumophila (Yamamoto et al, 2003;Suzuki et al, 2000).…”
Section: Treatmentmentioning
confidence: 99%
“…92 It has also been applied in medicine. 9396 Machine learning is applicable to a broad scope of acute care settings, including ED triage, 97 and the ICU. 98, 99 It is also applicable to specific diseases like sepsis 100103 and traumatic hemorrhage.…”
Section: Creating Physiologic Signatures Of Critical Illness Using Mamentioning
confidence: 99%